The nature of counselling with reference to Malaysian schools - Ahmad Sudan, Salmi (2019)
Counselling in education is comparatively a highly crucial field of study; especially in relation to school children as well as adults. This paper is a theoretical endeavor to assess the nature of counselling with special reference to Malaysian schools. School going children are in a molding stage and need guidance to become productive adults and contributive societal members. Counselling plays an immense role since these children are normally placed under a whole heap and enormous pressure. Besides, parents and society in general seem to place unbearable weight of expectations on children. Few nations and governments, in the third world, have taken serious initiatives to improve the situation; Malaysia is one of those nations. The subsequent governments of Malaysia have improved counselling services in the schools over the years. Nonetheless, more improvement is needed on the role of counselling in schools and educating the students on counselling services. The objective of this paper is to explicate the nature of counselling; its usefulness, and functions in the life of the individual. In fact, counselling makes reflective and deep impact on the lives of students, families and communities. This service assists individuals steer out of difficulties; and helps clients achieve their personal goals, and gain greater insight into their lives; as it is process of talking about and working through personal problems of the clients; it is more important in the school vicinity as the young minds need constant guidance to improve their personality.